Penerbitan obligasi & peran serta tanggung jawab wali amanat dalam pasar modal - Widjaja, Gunawan, 1969-; Jono, 1983- (Rawamangun, Jakarta : Kencana, 2006)
Issuance of bonds in Indonesian capital market
Includes bibliographical references (p. [125]-127)
Keywords: Bonds -- Law and legislation -- Indonesia; Capital market -- Indonesia